Using Randomized K Nodes Accept a New Node in Mobile Ad Hoc Wireless Network - Do, Dinh Thai; Tran, Ngoc Bao (Journal of Technical Education Science, 2009)
To accept a new node in mobile ad hoc wireless network with security scheme and high execution has been studying to find reasonable solution, especial, performing in mobile phone. Threshold k mutual authentication protocol in mobile ad hoc wireless network using randomized k nodes [3] also limit for new nodes join the network (these nodes is not belong to groups n nodes set up in the initial stage. We propose using randomized k nodes accept a new node in mobile ad hoc wireless network, which solves those problems using a combination of strong points in PSK (pre-share keys), PKI (public key infrastructure) and RSA. Our proposed accepting protocol is designed to implement in mobile phone – low configuration device. After a new node joined the network, it not only assume authentication role but also participate in authentication process.